2019
DOI: 10.1021/acs.energyfuels.9b03758
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation on NOx Generation Characteristic and Burnout Performance of Co-Combustion of Carbon-Based Solid Fuels under Deep-Staged Combustion

Abstract: With the development of low-rank coal chemical industry, the production of low-volatile carbon-based solid fuels, such as pyrolyzed and gasified semi-cokes, is ever-increasing. However, it is difficult to use such fuels efficiently because of their poor burnout performance and high NO x generation during the combustion process. Co-combustion of semi-cokes with bituminous coal is a promising approach for large-scale utilization of semi-cokes with ultra-low volatile content. Nevertheless, the NO x generation and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 43 publications
(78 reference statements)
0
3
0
Order By: Relevance
“…Wang et al evaluated the effects of the excess air coefficient in the primary combustion zone and the burnout air port position on the NO x emission and burnout ratio. Through years of research, simple depth air-staged combustion technology has been successfully applied in industrial pulverized coal boilers. , Recently, Wang et al tried to further reduce the NO x emission of depth air-staged combustion by cocombustion of carbon-based solid fuels. The experimental results indicated that blending bituminous coal could improve the combustion characteristics and reduce the NO x generation of semicoke. In addition, some scholars have investigated depth air-staged combustion under an oxygen-enriched atmosphere …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wang et al evaluated the effects of the excess air coefficient in the primary combustion zone and the burnout air port position on the NO x emission and burnout ratio. Through years of research, simple depth air-staged combustion technology has been successfully applied in industrial pulverized coal boilers. , Recently, Wang et al tried to further reduce the NO x emission of depth air-staged combustion by cocombustion of carbon-based solid fuels. The experimental results indicated that blending bituminous coal could improve the combustion characteristics and reduce the NO x generation of semicoke. In addition, some scholars have investigated depth air-staged combustion under an oxygen-enriched atmosphere …”
Section: Introductionmentioning
confidence: 99%
“…Currently, many scholars have paid attention to fuel-N conversion. Wang et al , investigated the fuel-N conversion path in deep air-staged combustion and proved that volatile-N could promote fuel-N conversion to N 2 . Bi et al proved that NH 3 could reduce NO x to N 2 and then increase the ratio of fuel-N converted to N 2 in the absence of O 2 .…”
Section: Introductionmentioning
confidence: 99%
“…The topic on cofiring of coal with highly volatile carbonaceous wastes is of interest to researchers due to the positive effect on the coal combustion and burnout performance. The cofiring of waste coal gangue, which contains 60–70% ash and 10–15% carbon in dry basis, with the coal has been conducted on the laboratory scale, and it was concluded that cocombustion is a good energy recovery pattern for the waste carbonaceous material utilization. The cofiring of gasified semicoke and bituminous coal was experimentally studied in a drop-tube furnace, and the effect of oxygen and combustion temperature on the unburned carbon of the semicoke was investigated. The blending ratio of semicoke when cofiring with the bituminous coal was recommended to be lower than 40% based on the burnout data in a DTF .…”
Section: Introductionmentioning
confidence: 99%